Task rescheduling model for resource disruption problem in unrelated parallel processor system - Nordin, Syarifah; Caccetta, Louis (AIP Publishing, 2014)
In this paper, we concentrate on the scheduling problem with interruption occurs in the parallel processor system. The situation happens when the availability of the unrelated parallel processors in the time slot decreases in certain time periods and its define as resource disruption. Our objective is to consider a recovery scheduling option for this issue to overcome the possibilities of having infeasibility of the original scheduling plan. Our approach for the recovery is task rescheduling which is to assign the tasks in the initial schedule plan to reflect the new restrictions. A recovery mixed integer linear programming model is proposed to solve the disruption problem. We also conduct a computational experiment using CPLEX 12.1 solver in AIMMS 3.10 software to analyze the performance of the model.